Impact of bismuth oxide on the structure, optical features and ligand field parameters of borosilicate glasses doped with nickel oxide. Issue 15 (1st August 2021) - Mansour, S.F.; Wageh, S.; Alotaibi, Maged F.; Abdo, M.A.; Sadeq, M.S.
Abstract: Understanding the impact of bismuth cations on the optical properties of borosilicate glass is significant for manipulating borate glass applications. In this paper, the influence of bismuth cations on both structural and optical properties of borosilicate glass doped with NiO was investigated. Different glass samples, containing different amounts of Bi2 O3 and a constant amount of NiO, were prepared and studied. Infrared (IR) analysis was carried out to study the internal structure within the investigated glass samples. Optical absorption studies were performed to investigate the impact of Bi2 O3 content on optical properties of the BiBaNiB-glasses. Astonishingly, with Bi2 O3 addition, an absorption band at 380 nm has appeared. Moreover, this band is overlapped with the Urbach edge; which regularly produced an artificial edge-like feature at 450 nm. A detailed deconvolution protocol has been implemented for an appropriate understanding of these spectra and unraveling the hidden Urbach edge. Optical band gap energy, linear and nonlinear refractive index for each BiBaNiB sample were calculated. Furthermore, the metallization criterion was calculated to examine the metallic or insulating nature of the BiBaNiB-glasses. The values of the nonlinear third-order susceptibility and nonlinear refractive index were increased with Bi2 O3 doping. The BiBaNiB-glasses exhibited outstanding stability and optical band gap than the pristine glass sample, which makes it possible for practical applications.